Analisa Potensi Bahaya Dengan Menggunakan Metode Job Safety Analysis (JSA) Pada Proses Coal Chain Di Pertambangan Batubara x Tahun 2014 - Muhammad Arif; Gerry silaban; Isyatun mardiah Syahri (Lingkungan dan Kesehatan Kerja, 2014)
An accident in the working place can be avoided by knowing and recognizing the various potential hazards that exist in the working environment. The most popular and most commonly used analysis method of the potential hazards in the working place is Job Safety Analysis (JSA). Job Safety Analysis (JSA) is a method of analysis towards potential hazards in working place by analizing working system and working procedure as well as human as the workers. This research is a descriptive survey that illustrated the safety analysis process using the Job Safety Analisys (JSA) with the aim to figure out the process that has the highest potential hazards. The object in this study is the coal chain process which consists of coal getting, coal crushing, coal hauling, and coal barging at PT Mifa Bersaudara mining in 2014. The research shows that coal barging is the most hazardous process of coal chain process. High level potential hazards exist as falling from altitude when climbing the ship body, stinged by high voltage electricity when turning on crusher machine, sabotage by villagers who block hauling road and the falling of bucket excavator to the hoper crusher. Researcher suggests to the management of PT Mifa Bersaudara mining to keep increasing the work safety and healthy by controlling various potential hazard in each process especially the coal chain. Keywords: Coal getting, coal crushing, coal hauling, coal barging, Job Safety Analisys (JSA)